Management of crisis or crisis of management? The Thai government's “policy as discourse” handling of the COVID-19 pandemic - Sukhampha, Rangsan; Kaasch, Alexandra (Frontiers in Political Science, 2023)
The complexity of crisis management in the context of COVID-19, which ranges from the global to the national, reveals a wide variety of means and ends, particularly at the national level. This triggered scholarly interest and raised questions regarding how central (authoritarian) governments handle the COVID-19 pandemic within state borders. The paper evaluates the Thai government's response to the COVID-19 pandemic from the beginning of 2020 to the middle of 2022, when the pandemic was declared over. We employ critical discourse analysis to explain Thailand's crisis management by engaging discursively with different population groups in the country. The findings indicate that the discursive policies and measures implemented by the government to deviate from and halt public pressure resulting from his mismanagement of vaccine policy are based on narratives related to national traditions as a means of resolving dilemmas rather than on the social needs of vulnerable individual citizens. We witnessed how discursive policies and measures can lead to other problems and ineffective responses, specifically regarding vaccine distribution. The article contributes to a better understanding of how, why, and to what extent discursive policies and measures were instrumentalized by an authoritarian government for COVID-19 crisis management, which can likely be inferred in similar cases in developing nations.